Cost-Effectiveness Analysis of Prostate Health Index in Decision Making for Initial Prostate Biopsy - Huang, Da; Yang, Xiaoqun; Wu, Yishuo; Lin, Xiaoling; Xu, Danfeng; Na, Rong; Xu, Jianfeng (Frontiers in Oncology, 2020)
Background: Clinical studies have suggested that prostate health index (phi) outperforms prostate-specific antigen (PSA) tests in prostate cancer detection. The cost-effectiveness of phi with different cutoffs is poorly understood in the context of decision making for prostate biopsy. Methods: In a multicenter cohort, 3,348 men with elevated total PSA (tPSA) underwent initial prostate biopsy from August 2013 to May 2019. We constructed a decision model to evaluate the incremental cost-effectiveness ratios of different phi cutoffs. Total costs and reimbursement payments were based on the fee schedule of Shanghai Basic Medical Insurance and converted into United States dollars ($). Two willingness-to-pay thresholds were estimated as one or three times the average gross domestic product per capita of China ($7,760 or $23,279, respectively). Results: The total costs of prostate biopsy and PSA tests were estimated at $315 and $19, respectively. The cost of phi test varied between $72 to $130 in different medical centers. Under different phi cutoffs (from 23 to 35), phi test predicted reductions of 420 (21.7%) to 972 (50.2%) in unnecessary biopsies, with a total gain of 23.77 to 57.58 quality adjusted life-years compared to PSA tests. All the cutoffs would be cost-effective for patients with tPSA levels of 2-10 ng/mL. Applying 27 as the cutoff was cost-effective for each tPSA range, with missing positive cases ranging from 11 (3.4%) to 33 (11.5%). Conclusions: Using phi test was cost-effective in the decision-making process for initial prostate biopsy, especially for patients with tPSA values between 2-10 ng/mL. The phi cutoff of 27 was cost-effective regardless of tPSA ranges and should be recommended from a health-economic perspective.